Self-efficacy and stress as predictors of anxiety in Peruvian and Mexican university students: a cross-sectional study - Anicama, José; Calderón, Raymundo; Javier-Aliaga, David; Caballero, Graciela; Talla, Karina; Pizarro, Ruth; Calizaya-Milla, Yaquelin E.; Saintila, Jacksaint (Frontiers in Education, 2025)
In recent decades, anxiety has increasingly affected the mental health of university students; however, few predictive studies have compared two countries in the Americas. This study examined stress and self-efficacy as predictors of anxiety among university students in Peru and Mexico. A cross-sectional study was conducted with 2,167 university students, including 1,160 from Peru and 1,007 from Mexico. The General Self-Efficacy Scale (GSES), the Communicable Disease Stress Scale (CDSS), and the Generalized Anxiety Disorder Scale (GAD-7) were utilized. Predictive analysis was conducted using multiple linear regression. The results indicated that Mexican students reported significantly higher levels of stress (M = 9.81, SD = 9.81, d = 0.277, p < 0.001) and anxiety (M = 9.46, SD = 9.46, d = 0.212, p < 0.001) compared to Peruvian students (stress: M = 8.89, SD = 3.04; anxiety: M = 8.39, SD = 4.86). In the regression analysis for Peruvian students, stress (β = 0.6072, CI [0.5602, 0.6541], p < 0.001) was the primary predictor of anxiety, followed by self-efficacy (β = −0.0765, CI [−0.1230, −0.0299], p < 0.001), sex (β = −0.0462, CI [−0.0907, −0.0018], p = 0.042), and age (β = −0.0906, CI [−0.1344, −0.0468], p < 0.001). For Mexican students (Model 2), stress (β = 0.685, CI [0.640, 0.7301], p < 0.001) and self-efficacy (β = −0.103, CI [−0.148, −0.0575], p < 0.001) remained significant predictors of anxiety, with stress having the greatest impact. The model explained 42.9% of the variance in anxiety among Peruvian students (adjusted R2 = 0.427) and 52.7% among Mexican students (adjusted R2 = 0.526). These findings underscore the need for interventions focused on enhancing self-efficacy and stress management, taking cultural factors into account, to reduce anxiety among university students.